Transforming Education: Insights from Differentiated Instruction In Indonesia - A Meta-Analysis - Andi Rahmat Saleh; Nur Aqidah Hafid (PT. Ininnawa Paramacitra Edukasi, 2025)
Differentiated instruction has become a key focus in the development of education in Indonesia. This research aims to determine the impact of differentiated instruction on student learning outcomes in Indonesia. This teaching approach is tailored to the individual needs, interests, and abilities of students. The study employs a meta-analysis method, utilizing 11 articles from Indonesian journals as research subjects. Based on the findings, it can be concluded that the implementation of differentiated instruction shows positive results in terms of learning materials, educational levels, research regions, different time spans, and types of implementations such as models, approaches, and strategies. The data indicate that differentiated instruction can improve student learning outcomes, as it is one solution for addressing differences in students' learning styles